2020
DOI: 10.1007/s00167-020-06185-0
|View full text |Cite
|
Sign up to set email alerts
|

Tibial tray cementation is not necessary for knee revision with titanium metaphyseal sleeves: a mid-term prospective study in AORI 2B defects

Abstract: PurposeMetaphyseal fixation with porous titanium sleeves in revision knee surgery provides mechanical support to the implant, promotes biological fixation, and has shown satisfactory short‐ and mid‐term results. Cement is commonly used to fix the tibial tray to the epiphyseal area. The objective of this study is to determine whether cement should be used to achieve fixation of the tibial tray with the hypothesis that metaphyseal sleeves would provide enough axial and rotational stability making cementation unn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Cones or sleeves for both femur and tibia were used in 22 studies [1, 7, 10, 11, 13, 17, 18, 21, 22, 24–26, 29, 30, 33, 34, 42, 50, 54, 56, 58, 60], solely on the tibial side in seven studies [3, 5, 14, 28, 31, 35, 44] and on the femoral side in one study [51].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cones or sleeves for both femur and tibia were used in 22 studies [1, 7, 10, 11, 13, 17, 18, 21, 22, 24–26, 29, 30, 33, 34, 42, 50, 54, 56, 58, 60], solely on the tibial side in seven studies [3, 5, 14, 28, 31, 35, 44] and on the femoral side in one study [51].…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies [5, 11, 13, 21, 22, 25, 29, 33, 42, 50, 60] reported intraoperative and postoperative fractures comprising a total of 48 out of 1032 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation